CHILDREN WORKSHOPS ABOUT ARCHITECTURE BY PRIVATE MUSEUMS IN ISTANBUL - Akbulut, Dilek Eksi; Ciftci, Aynur; Akbulut, M. Tolga (IATED-INT ASSOC TECHNOLOGY EDUCATION A& DEVELOPMENT, 2013)
This paper covers a research on children workshops about architecture, which are organized by private museums in Turkey. In this context, 3 private foundation museums in Istanbul have been taken. These museums are Istanbul Modern, Sabanci Museum, Koc Museum. The activities of Koc Museum about architecture are The Architect Sinan's Secret (practicing how to construct a simple archway), which has been created for the activity Colorful Mathematical World-Learn and Have Fun, Can You Build Leonardo's Halic Bridge (building a model bridge out of wooden elements) and Puzzle activities (bringing different geometrical objects together to complete a whole figure). The activity Here Comes the Sun, offers school children the opportunity to design energy-saving model houses and bring these together to build the power city of tomorrow. The museum Istanbul Modern offers children the architectural activity Designing Spaces for Domestic Animals. In this activity, children are asked to design houses for their real or virtual pets-cats and animals-with the materials given. The key activity of Sabanci Museum about architecture is related to an exhibition named Legendary Istanbul: From Byzantine to Istanbul - 8000 Years of a Capital. In this exhibition, children are given information by expert guides about the rich cultural heritage of Istanbul, the capital of Byzantine and Ottoman Empire, and then at a workshop they are asked to draw pictures about Istanbul. In this paper, architectural activities organized by the relevant museums will be discussed, assessing the interviews with the museum instructors and examining the results of a survey made up of 16 questions. These questions are based on the reason of choosing the activities related to architecture as well as their duration, scope, content, frequency and the feedback given by children at the end of the activities. The paper ends with findings and implications.
Keywords: Museum activities; architecture; education; children; architectural education; design; Education & Educational Research